Social Mobilizations of a Changing Era. The Yellow Vests Movement in France - Núñez Cruz, Maribel (Revista Mexicana de Ciencias Políticas y Sociales, 2021)
Social Movement theories currently face the challenge of explaining a new kind of social movement, different from those of industrial societies and the so-called New Social Movements. Mobilizations like those of the Yellow Vests in France are network movements because of their intensive use of social networks. They are also characterized by their distancing from traditional political actors such as political parties and trade unions. Another particularity is that they do not admit or build leaderships that are recognized by all participants. They also bring together people whose ideas identify with the far right, the far left or neither, which is why these movements have been deemed post-ideological. They often move away from a mobilization style that is considered politically correct, and sometimes justify the use of violence. Lastly, their demands are considered unspecific and even contradictory, but they constitute movements that contribute to the empowerment of precarious sectors that are marginalized from political and economic decisions, as well as to the questioning of the cultural hegemony of the upper classes.